Holidays abroad of Dutch citizens do not increase their appetite for greater European integration - Juan Díez Medrano; Juan J. Fernández (Annals of Tourism Research Empirical Insights)
What is the relationship between international travel and pro-European dispositions? Most theoretical research on European integration argues that international travel fosters these dispositions, and many cross-sectional studies support this expectation. However, support for this association rests on strong and questionable micro-foundational assumptions. This article critically engages with the association between international travel and pro-European dispositions. To do so, we draw on social psychology models and tourism research, which emphasize that the quality and impact of travel experiences are highly heterogeneous and contingent on individual, interactional, and contextual factors. Building on these perspectives, we predict no association between international travel and support for further European integration. To test this prediction, we use panel data from the Netherlands and employ two-way fixed-effects models to evaluate both the positive and negligible association hypotheses. In line with our prediction, we find that among Dutch citizens, within-individual increases in the number of international trips are not significantly related to changes in support for European integration. In summary, evidence from a rigorous test does not support the claim that typical international travel fosters pro-European dispositions.